2020
DOI: 10.3390/joitmc6040127
|View full text |Cite
|
Sign up to set email alerts
|

The Balance between Work and Life for Subjective Well-Being: A Moderated Mediation Model

Abstract: The aim of this study is to investigate the association among work-life balance, intrinsic motivation, subjective well-being and job satisfaction among the healthcare professionals of Pakistan. Utilizing a sample of 301 Health Care Professionals, the authors tested the proposed relationships. Findings were constant with the hypothesized theoretical scheme, and mediated association between work-life balance and subjective well-being through job satisfaction was stronger when intrinsic motivation was high rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…It is higher mental health, behavioral styles of self-improvement, and interpersonal connection. Prior studies have determined that factors can improve the subjective well-being of employees i.e., i.e., thriving, civility, fairness perception [ 48 ], flourishing, energy [ 49 ], ethical leadership, voice behavior [ 50 ], and work/life balance [ 51 ], while the influence of workplace incivility on employee subjective wellbeing was not explored. So, we posit:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…It is higher mental health, behavioral styles of self-improvement, and interpersonal connection. Prior studies have determined that factors can improve the subjective well-being of employees i.e., i.e., thriving, civility, fairness perception [ 48 ], flourishing, energy [ 49 ], ethical leadership, voice behavior [ 50 ], and work/life balance [ 51 ], while the influence of workplace incivility on employee subjective wellbeing was not explored. So, we posit:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…As in most of Europe, Slovenia is also facing the challenge of sedentary behavior as part of modern work conditions. This is the first time that Slovenian enterprises were researched in terms of sedentary work conditions, concerning job satisfaction, life satisfaction and well-being on work performance, which is the main novelty of the work and presents the possibility of comparing findings with other studies [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ], such as the effect of COVID-19 [ 5 , 47 ], remote job options and cross-country differences [ 53 ] or socio-economics status in the relationship between leadership and well-being [ 54 ]. The main gaps, which are supplemented by our studies, are, in addition to finding the correlations between some factors and work performance in sedentary jobs, encouraging similar further studies with the final goal of determine the factors that correlate most with job performance in sedentary work conditions.…”
Section: Discussionmentioning
confidence: 95%
“…It has also been found that sedentary behavior negatively correlates with an active lifestyle [ 4 , 6 ] and with less effective work performance [ 14 , 35 ], which also supports our conclusions. Furthermore, our systematic observation findings indicate specific problems in the organizational climate among employees and point to a significant division between the groups and consequential low team cohesiveness, which is essential for team or group effectiveness and work performance [ 50 ]. In our study, the group of employees who were willing to participate called themselves ‘cooperative employees’, whereas employees who were not ready to take part in this study were referred to as ‘those others’, those who never cooperate and always complain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations